78 INTESTINAL METAPLASIA IN THE ESOPHAGEAL REMNANT IS RARE AFTER IVOR LEWIS ESOPHAGECTOMY. (14th September 2020) - Corsini, E; Mitchell, K; Zhou, N; Antonoff, M; Mehran, R; Rajaram, R; Rice, D; Roth, J; Sepesi, B; Swisher, S; Vaporciyan, A; Walsh, G; et al.
Abstract:  : Most patients undergoing esophagectomy will experience intermittent reflux of gastric and biliary content into the remnant esophagus over the course of their lives. The incidence of new or recurrent intestinal metaplasia (IM) following chemoradiation and surgery has not been well-described. Furthermore, post-resection guidelines do not exist regarding surveillance for IM in the esophageal remnant. We hypothesized that the incidence of IM in patients who underwent active post-treatment surveillance would be low. Methods: Patients undergoing Ivor Lewis esophagectomy after concurrent chemoradiation for a diagnosis of esophageal adenocarcinoma at a single institution from 2006–2018 were identified. Pathology records were reviewed for the presence of IM on pretreatment biopsies, surgical specimen, or post-resection biopsies. Categorical variables were compared using Pearson's chi-square test or Fisher's exact test, where appropriate, and continuous variables were compared using Kruskal-Wallis test. Time-to-event outcomes were assessed using the Kaplan–Meier method. Results: 621 patients were included, and 242 (39%) were known to have had IM prior to esophagectomy. An additional 26 (4%) patients without a preexisting diagnosis of IM were found to have IM in the surgical specimen. During a median follow-up of 62 months, development of new IM was rare, occurring only in 12 (2%) patients, 7 of whom had a prior history of IM(Table); incidence was 0.6 cases per patient-years. Of these 12, 3 (25%) developed local adenocarcinoma recurrence. Overall, local recurrence of adenocarcinoma was uncommon, and occurred at similar rates in patients with and without a history of IM(p = 0.774). Conclusion: Despite several factors predisposing to mucosal damage following esophagectomy, occurrence of new IM after trimodality therapy in our patient population appears to be rare, even among patient with a previous history of metaplasia.